Anxieties about knowing in the context of work discussion: questions of difference*. Issue 1 (2nd January 2018) - Crehan, Geraldine; Rustin, Michael
ABSTRACT: The authors address why issues of difference in identity may be difficult to explore in the context of Work Discussion Seminars. Consideration is given to the importance of finding ways of reflecting on the phenomena of difference which makes use of a psychoanalytic frame of reference. Attention is also paid to the heightened levels of anxiety that are generated when thinking about diverse identities and an illustrative vignette is given by way of example. It is proposed that a specific form of anxiety, named here as epistemic anxiety, may be evoked by learning that threatens existential security and a stable sense of identity. The authors suggest that epistemic anxiety is especially relevant for understanding why issues of ethnicity and difference may not always be adequately examined in Work Discussion Seminars.